Fabrication and Analysis of Bio-Inspired Smart Surfaces - Röhrig, Michael (Schriften des Instituts für Mikrostrukturtechnik am Karlsruher Institut für Technologie / Hrsg.: Institut für Mikrostrukturtechnik, 2013)
This work introduces novel techniques for the fabrication of bio-inspired hierarchical micro- and nanostructures. The enormous potential of these techniques is demonstrated by presenting a synthetic gecko-like adhesive matching the adhesion and self-cleaning of geckos very closely and a nanofur which is superhydrophobic, superoleophilic, underwater air-retaining, and even self-healing when surface treated.